Methodology of Applying Modular Teaching Technology in the Science of Life Safety - Dustkabilovich, Rahimov Oktyabr; Laylo, Ashurova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article depicts the basic content of the quality of education and its criteria, self education and distance learning, its teaching methods, integrated approach to teaching, technology of creating modular teaching materials, the essence of modular teaching, modularity, the structure of the module, the composition of elements.